THE STORY OF A LIFE*. Issue 1 (12th February 2014) - Rosati, Connie S.
Abstract: This essay explores the nature of narrative representations of individual lives and the connection between these narratives and personal good. It poses the challenge of determining how thinking of our lives in story form contributes distinctively to our good in a way not reducible to other value-conferring features of our lives. Because we can meaningfully talk about our lives going well for us at particular moments even if they fail to go well overall or over time, the essay maintains that our good must consist in something more than an accumulation of good discrete moments. Since persons have the capacities to reason, remember, and imagine, our good depends on a larger view of our lives that integrates its particular moments in a narrative. That narrative provides shape and texture to our lives. Storytelling serves to connect the events of our lives to each other, and to explain why the meaning and value of past events or features of our lives can shift as the life, and hence the story of the life, continues to unfold. The essay concludes that narrative enables us to see our lives in ways that support, encourage, or promote our self-concept and self-worth as agents who have controlling authority over our own lives.